SabaTracheid 1.0: A Novel Program for Quantitative Analysis of Conifer Wood Anatomy — A Demonstration on African Juniper From the Blue Nile Basin - Gebregeorgis, Eyob Gebrehiwot; Boniecka, Justyna; Pia̧tkowski, Marcin; Robertson, Iain; Rathgeber, Cyrille B. K. (Frontiers in Plant Science, 2021)
Knowledge about past climates, especially at a seasonal time scale, is important as it allows informed decisions to be made to mitigate future climate change. However, globally, and especially, in semi-arid Tropics, instrumental climatic data are scarce. A dendroclimatic approach may fill this gap, but tropical dendrochronological data itself is also rare and does not yet provide fine resolution intra-annual information about past climates. Unlike in the Tropics, in Mediterranean, temperate, alpine, and arctic regions, dendroanatomy and quantitative wood anatomy (QWA) are progressing fast attaining an intra-annual resolution, which allows a better understanding of seasonal climate dynamics and climate–growth relationships. The existing dendroanatomical and QWA methods aren’t suitable for tropical trees because they do not consider the high variation in tree ring width and the frequent occurrence of micro-rings containing only a few tracheids per radial file. Thus, the available tracheid analysis programs generally fail to provide multiple sectors for micro-rings and they are unable to compute most of the useful dendroanatomical parameters at fine temporal resolutions. Here we present a program (SabaTracheid) that addresses the three main standard tasks that are necessary for QWA and dendroanatomy before launching a climate analysis: (1) tracheidogram standardisation; (2) sectoring, and (3) computing QWA and dendroanatomical variables. Here, SabaTracheid is demonstrated on African juniper (Juniperus procera Hochst. ex Endl), but it is potentially able to provide fine-resolution QWA and dendroanatomic data that could be used for dendroanatomical studies in all regions of the world. SabaTracheid is a freeware that quickly and accurately standardises tracheidograms, divides tree rings into multiple regular sectors, computes useful dendroanatomic and QWA variables for the whole tree rings, or early and latewood portions, or each sector separately. This program is particularly adapted to deal with high inter-annual growth variations observed in tropical trees so that it assures provision of complete sectoral QWA and dendroanatomical data for micro-rings as well. We demonstrate SabaTracheid using 30 Juniperus procera tree rings from the Blue Nile basin, in Ethiopia. SabaTracheid’s ability to provide fine-resolution QWA and dendroanatomic data will help the discipline develop in tropical as well as in Mediterranean and temperate regions.